2015
DOI: 10.3389/fpls.2015.00799
|View full text |Cite
|
Sign up to set email alerts
|

Plant derived substances with anti-cancer activity: from folklore to practice

Abstract: Plants have had an essential role in the folklore of ancient cultures. In addition to the use as food and spices, plants have also been utilized as medicines for over 5000 years. It is estimated that 70–95% of the population in developing countries continues to use traditional medicines even today. A new trend, that involved the isolation of plant active compounds begun during the early nineteenth century. This trend led to the discovery of different active compounds that are derived from plants. In the last d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
233
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 356 publications
(237 citation statements)
references
References 133 publications
(179 reference statements)
0
233
0
4
Order By: Relevance
“…Natural products are an alternative resource widely accepted because of the diversity regarding the structure and the biological mechanism of action, their compounds being widely used in cancer therapy . Several plant‐derived compounds with anticancer properties have been described.…”
Section: Introductionmentioning
confidence: 99%
“…Natural products are an alternative resource widely accepted because of the diversity regarding the structure and the biological mechanism of action, their compounds being widely used in cancer therapy . Several plant‐derived compounds with anticancer properties have been described.…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin, an ingredient found in the spice turmeric, has been suggested to have antiproliferative, anticancer, proapoptotic, and antioxidant properties in cancer [61]. It is currently being studied for use in many different cancers targeting tumor cells and the tumor microenvironment which is very important in the prevention and treatment of the disease.…”
Section: Dietary Regulation Of Non-coding Rnas and Cancer Preventionmentioning
confidence: 99%
“…The World Health Organization (WHO) reported that one-third of the world's population has no access to medical care, relying primarily on the use of traditional remedies [2]. It was also reported that 70-95% of the world's total population still depends on traditional medicines for their primary health care needs [3,4].They are important sources of diverse bioactive and therapeutic compounds. Natural products represent about fifty percent of all clinically used drugs [5].…”
Section: Introductionmentioning
confidence: 99%